PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Hoka Hoka Bento “HokBen” Tangcity Malldi Tangerang) - Raditya Firmansyah; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The purpose of this research is to determine the influence of price perceptions, product quality and promotion on purchasing decisions at the HokBen Tangcity Mall in Tangerang. In this research, the population is consumers of HokBen Tangcity Mall in Tangerang. The sample in this study amounted to 96 respondents. The sampling technique used in this research is the Non Probability Sampling technique using a Purposive sampling technique approach.The analysis tool used is SPSS 26. The results of the research are that perceptions of price, product quality and promotion have a significant influence on purchasing decisions at the HokBen Tangcity Mall in Tangerang.